The intersections of comedy and politics in Zimbabwe: analysing Baba Tencen’s ‘Borderphobia’ and Prosper Ngomashi’s ‘Pastor and his wives’ - Charles Tembo; Allan T. Maganga; Tevedzerai Gijimah (Taylor and Francis Online, 2023)
Absract